2012
DOI: 10.5194/nhess-12-1119-2012
|View full text |Cite
|
Sign up to set email alerts
|

Flood modelling with a distributed event-based parsimonious rainfall-runoff model: case of the karstic Lez river catchment

Abstract: Abstract. Rainfall-runoff models are crucial tools for the statistical prediction of flash floods and real-time forecasting. This paper focuses on a karstic basin in the South of France and proposes a distributed parsimonious event-based rainfall-runoff model, coherent with the poor knowledge of both evaporative and underground fluxes. The model combines a SCS runoff model and a Lag and Route routing model for each cell of a regular grid mesh. The efficiency of the model is discussed not only to satisfactorily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 36 publications
(34 reference statements)
0
54
0
1
Order By: Relevance
“…For instance, in rainfall-runoff modelling, it has been demonstrated that the wetness condition of the catchment before a flood event strongly controls the severity of the response of the catchment in terms of runoff [1][2][3][4]. In other words, different initial soil moisture conditions can discriminate between catastrophic and minor effects for the same amount of rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in rainfall-runoff modelling, it has been demonstrated that the wetness condition of the catchment before a flood event strongly controls the severity of the response of the catchment in terms of runoff [1][2][3][4]. In other words, different initial soil moisture conditions can discriminate between catastrophic and minor effects for the same amount of rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 1 in Coustau et al, 2012) -both empty at the beginning of the event. The cumulated rainfall reservoir has an infinite capacity and determines the direct runoff using a runoff coefficient derived from the SCS runoff model, as used by Gaume et al (2004):…”
Section: The Hydrological Modelmentioning
confidence: 99%
“…This model combines a Soil Conservation Service derived (SCSderived) runoff function with a "lag-and-route" routing function. SCS-LR model was presented in Coustau et al (2012), and will be briefly summarized as follows:…”
Section: The Hydrological Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…as the forcing variables. Coustau et al [16] reported that the initial wetness condition (IWC) derived from the simulated soil moisture significantly improved most of the flood simulations in the event-based rainfall-runoff model.…”
Section: Introductionmentioning
confidence: 99%